Genre-specific Writing Motivation in Late Elementary-age Children: Psychometric Properties of the Situated Writing Activity and Motivation Scale - Gary A. Troia; Frank R. Lawrence; Heqiao Wang (SAGE Open)
Writing motivation is a multidimensional construct that has been demonstrated to be of great importance in writing performance and growth. Yet, much of the extant research has failed to examine the nuances of the various dimensions of writing motivation—in particular, task competency beliefs—and has neglected to investigate how the various dimensions are related to writing performance across different genres of writing. Our goals in this study were to (a) evaluate the latent structure, reliability, and criterion validity (using essay writing quality as the criterion measure) of the Situated Writing Activity and Motivation Scale (SWAMS), an instrument developed to include more nuanced items related to genre-specific task-related versus skill-related writing motivational beliefs and outcome versus efficacy expectations; (b) determine if writing motivation measured by the SWAMS was different across narrative, informative, and persuasive genres; and (c) to identify potential differences in writing motivation attributable to sample sociodemographic characteristics. The SWAMS was pilot tested with a sample of 397 students in grades 4 and 5 classrooms to gather data used to address our research goals. Overall, our results indicated that the narrative, informative, and persuasive subscales of the SWAMS exhibited acceptable psychometric properties, though there were issues related to unidimensional model fit and item bias. A significant amount of unique variance in narrative, informative, and persuasive writing quality was explained by motivation for writing in each genre, suggesting predictive criterion validity. Although we did not observe genre-based differences in overall motivation to write using summative scores for each subscale, there were small but significant differences between narrative and informative writing for the discrete motivational constructs of self-efficacy, outcome expectations, and task interest and value. Consistent differences favoring girls and students without special needs were observed on SWAMS scores, apparently linked with observed differences in writing performance. Further refinement of this instrument is recommended to strengthen its psychometric properties, but in its current form, the SWAMS may be useful to researchers and practitioners interested in examining late elementary-aged students’ genre-specific writing motivation.